Reproducibility of cephalometric measures obtained by dental radiologists - Nádia Assein Arús; Gabriela Salatino Liedke; Mathias Pante Fontana; Reni Raymundo Dalla-Bonna; Heraldo Luis Dias da Silveira; Heloísa Emília Dias da Silveira (Universidade Federal do Rio Grande do Sul. Faculdade de Odontologia, 2011)
Cephalometric analysis is used by dentists to assist in the diagnosis, planning and follow-up of orthodontic, orthopedic and surgical treatments. However, cephalometry is not a precise tool, and there are significant errors in the measures obtained by the same or different examiners. Objectives: The purpose of this study was to evaluate the reproducibility of cephalometric measures obtained by three specialists in oral radiology, and to compare them with the results obtained by three radiology clinics. Materials and Methods: Examiners traced cephalograms from 39 conventional cephalograms from the sample used by Silveira e Silveira (2006). ANOVA revealed good reproducibility of 17 of the 32 factors in the analyses conducted by dental specialists. Results: Agreement between dental specialists was found for 53.1% of the factors, whereas agreement for the results obtained by radiology clinics was only 12.5%. Conclusion: Results showed that tracings by the 3 radiology specialists had greater agreement than those by the radiology clinics under study.